التعريف بأهم المؤلفات في السياسة الشرعية: دراسة وصفية - الغامدي، ناصر بن محمد بن مشري (ديوان الوقف السني - مركز البحوث والدراسات الإسلامية, 2022)
هذا بحث علمي للتعريف بأهم المؤلفات في علم السياسة الشرعية؛ إذ إن هذه المسألة من المسائل المهمة التي يحتاجها طلاب العلم، ولاسيما التخصصات القضائية والسياسة الشرعية، حتى يعرفوا مصادر العلم، وتمايزها فيما بينها، والسابق الأصل من اللاحق التبع، وفضلا عن أن مسائل وموضوعات علم السياسة الشرعية متعددة، وبعض المؤلفات المهمة فيه تأتي ضمن فنون علمية مختلفة؛ بعضها: ضمن مؤلفات الأدب، وبعضها ضمن مؤلفات التاريخ والحضارة، وبعضها ضمن مؤلفات الوعظ والإرشاد، فيحسن بطالب العلم معرفة هذه المؤلفات، ومراتبها وأهميتها وأهمها، وهو ما ركز عليه هذه البحث مختصرا في التعريف بهذه المؤلفات، وتقسيمها حسب مراحل التأليف فيه. جاء البحث في مقدمة، وأربعة مباحث: الأول عن المؤلفات في مرحلة النشأة والاستقلال في التأليف؛ والثاني عن المؤلفات في مرحلة التميز والنضج والشمول؛ والثالث عن المؤلفات في مرحلة التأصيل والتنظيم والتقعيد؛ والرابع عن المؤلفات في مرحلة النهضة الحديثة والتخصص، ثم خاتمة بأهم النتائج وفهرس بالمراجع والمصادر. This is a scientific research to introduce the most important literature in the science of legal politics. Since this issue is one of the important issues that students of science need, especially judicial disciplines and legal politics, so that they know the sources of knowledge, their differentiation among them, and the preceding origin from the later to follow, in addition to the fact that the issues and topics of legitimate political science are numerous, and some of the important literature on it comes within the arts different scientific; Some of them are within the literature, some are within the books of history and civilization, and some are among the books of preaching and guidance, so it is good for the student of knowledge to know these books, their ranks, importance and most important, which is what this research focused on briefly in the definition of these works, and their division according to the stages of authorship in it. The research came in an introduction, and four topics: the first is about literature in the stage of infancy and independence in authorship; The second is about literature in the stage of excellence, maturity and comprehensiveness. The third is about compositions in the stage of rooting, organizing and tying; The fourth is about the literature in the modern renaissance stage and specialization, then a conclusion with the most important results and an index of references and sources.
Keywords: العلوم الشرعية -- الفكر السياسي -- السياسة الإسلامية -- الفقه الإسلامي